PHYTOCHEMICAL STUDIES OF Acacia catechu - Baluja, Shipra; Chanda, Sumitra; Solanki, Asif; Kachhadia, Nikunj (Indonesian Journal of Pharmacy, 2012)
Acacia  catechu Willd.  belongs  to  the  family  Mimosaceae.  It is well known for the powder of wood known as Kathha” in India, which  has  wide  applications.  In  the  present  work,  the  dry  wood powder  is  extracted  in  various  solvents  such  as  1,4-dioxane, methanol,  dimethyl  formamide  (DMF),  acetone,  ethanol  and distilled water. The phytochemical and physicochemical properties of  these  various  solvent  extracts  were  studied.  The  phyto constituents  present  in  the  different  extracts  were  saponins, tannins,  sugars,  terpenes,  catechu-tannic  acid.  Alkaloids  were present  in  organic  solvents  only.  The  antibacterial  activity  of  all the extracts in DMSO was studied against five bacterial strains but none of the extracts inhibit any of the studied bacterial strains.Key  words: Acacia  catechu,  1,4-dioxane,  methanol,  dimethyl  formamide (DMF),  acetone,  ethanol,  distilled  water,  phytochemical analysis, physicochemical analysis.